The Role of the Toll-Like Receptor Signaling Pathway in Autoimmune Diseases and Treatment with Traditional Chinese Medicine: A Literature Review - Wang, Yaru; Bao, Lin; Liu, Mingying; Tang, Xintian; Liu, Hui; Liang, Xiaodong; Liu, Yifan (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2025)
Toll-Like Receptors (TLRs) is a pattern recognition receptor that connects innate and adaptive immunity and participates in inflammatory responses play a key role in common autoimmune diseases such as Rheumatoid Arthritis (RA), systemic lupus erythematosus (SLE), psoriasis, and Sjögren’s syndrome (SS) by participating in antigen recognition, immune cell activation, and inflammatory factor release. Due to the multi-component and multi-target characteristics of traditional Chinese medicine (TCM), the role of TCM active ingredients acting on TLRs has been widely studied. This article describes the relationship between TLR and four autoimmune diseases, as well as a review of the efficacy of TLR intervention by active ingredients of traditional Chinese medicine. To provide some basis for the future clarification of the mechanism of action of drugs for autoimmune diseases and to assist in the development of new medicines.
Keywords: rheumatoid arthritis